2020
DOI: 10.3389/fpls.2020.00142
|View full text |Cite
|
Sign up to set email alerts
|

SaHsfA4c From Sedum alfredii Hance Enhances Cadmium Tolerance by Regulating ROS-Scavenger Activities and Heat Shock Proteins Expression

Abstract: The heat shock transcription factor (Hsf) family, an important member in plant stress response, affects cadmium (Cd) tolerance in plants. In this study, we identified and functionally characterized a transcript of the Hsf A4 subgroup from Sedum alfredii. Designated as SaHsfA4c, the open reading frame was 1,302 bp long and encoded a putative protein of 433 amino acids containing a complete DNA-binding domain (DBD). Heterologous expression of SaHsfA4c in yeast enhanced Cd stress tolerance and accumulation, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…To defend plant cells from oxidative injury, plants have developed various detoxification systems including ascorbic acid, water-soluble reductants, glutathione, as well as antioxidant enzymes involving ROS scavengers, such as POD, CAT, and APX [ 63 , 64 ]. Previous studies have strongly demonstrated the connection between antioxidant enzymes and Hsfs in scavenging ROS [ 63 , 65 , 66 ]. For instance, Arabidopsis Hsf3 was involved in modulating the expression of APX2 to scavenge H 2 O 2 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To defend plant cells from oxidative injury, plants have developed various detoxification systems including ascorbic acid, water-soluble reductants, glutathione, as well as antioxidant enzymes involving ROS scavengers, such as POD, CAT, and APX [ 63 , 64 ]. Previous studies have strongly demonstrated the connection between antioxidant enzymes and Hsfs in scavenging ROS [ 63 , 65 , 66 ]. For instance, Arabidopsis Hsf3 was involved in modulating the expression of APX2 to scavenge H 2 O 2 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the metal(oid) uptake and/or transport was reported to be more a quantitative trait subject to crosstalk of multiple genes and the regulation of HM transport/tolerance in plants requires more than one physiological pathway (8), of particular interest, the transcriptional expression pattern of an aquaporin gene and analogue mechanisms of one of the enzymatic antioxidants (peroxidase1) and stress proteins, protecting enzyme malfunction (HSP1) were chosen to be analyzed and confirmed by quantitative PCR. While PODs are one of the major enzymatic antioxidants catalyzing the breakdown of H 2 O 2 to scavenge radicals, or sometimes generating H 2 O 2 themselves as signal molecules (34), the HSPs are the quality controllers of PODs , assisting conformational changes (35). They belong to multi-gene superfamilies whose proteins are present in the mitochondria or chloroplasts showing induced expression not only by thermostress but also by HMs (35).…”
Section: Discussionmentioning
confidence: 99%
“…To find evidence for a possible connection and/or interlinking between combined HM stress, TS143 bio-stimulation, and plant response against an oxidative burst caused by ROS, four experimental groups with maize seedlings were prepared to test the protection potential of the target strain under As, Cd, Cu, Pb, Znapplied conditions. In this context, the mRNA expression profiles of previously identified defense gene expressions reported to be induced by different HMs (34) were analyzed (yet, despite these proteins conferring putative trace element caused stress tolerance, HSP, PIP, and POD-encoding genes cannot be listed as sole protection components for HMs). Activation under HM mix conditions in the gene encoding ZmPIP1-5 (1.40-fold), ZmHSP1 (1.8fold) and ZmPOD1 (5.55-fold) respectively showed molecular evidence of cellular damage that overlapped with phenotypic changes (Figure 2).…”
Section: Hm Cocktail Alters Response Patterns Of Plasma Intrinsic Protein Peroxidase and Heat Shock Defense Genes In Maizementioning
confidence: 99%
“…HSP maintains normal cell metabolism by upregulating the activity of ROS scavenging enzymes (including antioxidant enzymes), reducing ROS accumulation, and removing denatured proteins. It can also bind to cytoplasmic phosphorylated proteins to regulate antioxidant enzyme activity, induce melatonin production, and upregulate MT expression, thereby improving the ability of cells to tolerate Cd [ 157 , 158 , 159 ], which may be related to the DNA-binding domain in the heat shock transcription factor, HsfA4a [ 160 ]. In addition to the synthesis of HSP, plants can also induce ethylene production under Cd stress.…”
Section: The Mechanisms Of Plant Enrichment Of CDmentioning
confidence: 99%